Novel alpha-7-oxy-4-(4-methoxyphenyl)-8-methylcoumarin substituted metal-free, Co(II) and Zn(II) phthalocyanines: Photochemistry, photophysics, conductance and electrochemistry - Odabas, Zafer; Orman, Efe Baturhan; Durmuş, Mahmut; Dumludag, Fatih; Ozkaya, Ali Riza; Bulut, Mustafa (Elsevier Sci Ltd, 2012)
Novel alpha-substituted metal-free. Co(II) and Zn(II) phthalocyanines, bearing four 7-oxy-4-(4-methoxyphenyl)-8-methylcoumarin moieties were synthesized. The compounds were characterized by elemental analysis, IR, UV vis, H-1 NMR, C-13 NMR and MALDI-TOF mass spectroscopies. The Zn(II) phthalocyanine compound showed J-type aggregation in non-coordinating solvents. The photophysical and photochemical properties of these compounds were described in different solvents. Direct current conductivity measurements of the films of Co(II) and Zn(II) phthalocyanines as a function of temperature showed that these compounds are semiconductors with the activation energies within the range of 0.40-0.84 eV. The variation of alternating current conductivity of the films with frequency was found to be represented by the function sigma(AC) = A omega(s). The results indicated that charge transport mechanism of the films can be explained by hopping. The redox properties of the compounds were also examined in dimethylsulfoxide and dichloromethane by voltammetry and in situ spectroelectrochemistry. The compounds displayed metal and/or phthalocyanine ring-based reduction and oxidation processes. The electrochemistry of a phthalocyanine compound forming a J-aggregated species has been investigated. It was found that some redox couples of the Zn(II) compound in dichloromethane is split due to the equilibrium between its aggregated and non-aggregated species. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Phthalocyanine; Electrochemistry; J-aggregation; Photophysics; Semiconductor; Photochemistry